Review of Islamic Law on Test Tube Babies and Artificial Insemination - Livia Maylisandi; Muhammad Raja; Hanif Rahman Adhyaksa (ISNU Sumatera Utara, 2025)
This article discusses the phenomenon of in vitro fertilization (IVF) and artificial insemination as part of advances in reproductive technology from the perspective of Islamic jurisprudence. Advances in medical science have enabled couples experiencing difficulty conceiving children to achieve childbearing through scientific methods. However, in Islam, all medical interventions must remain within the bounds of Islamic law, particularly in terms of maintaining lineage, family honor, and marital law. This study aims to explore the limitations and legal provisions regarding the permissibility of IVF and artificial insemination practices in Islamic jurisprudence. The research was conducted through a literature review of fatwas from the Indonesian Ulema Council (MUI), the opinions of contemporary scholars such as Yusuf al-Qaradawi, Wahbah azZuhaili, and international fatwa institutions. The results of the study indicate that IVF and artificial insemination are permissible in Islam if they use sperm and ovum from a legally married couple and do not involve third-party donors or surrogate mothers. In conclusion, Islam does not reject modern medical technology as long as it does not conflict with the basic principles of Islamic law, such as maintaining lineage, honor, and clarity of lineage.